Chromosomal localization and expressed sequence tag generation of clones from a normalized human adult thymus cDNA library. - Lamerdin, J E; Athwal, R S; Kansara, M S; Sandhu, A K; Patanjali, S R; Weissman, S M; Carrano, A V (Genome Research, 1995)
Expressed sequence tags (ESTs) from 298 clones have been generated from a randomly primed, normalized human adult thymus cDNA library. We describe the chromosomal localization of 136 of these ESTs by PCR-based mapping to a human monochromosomal somatic cell hybrid panel. Data base similarities to known genes are also described. A subset (n = 18) of these randomly primed ESTs extended the sequence of ESTs from other tissues currently in dbEST. Of the nonrepetitive human adult thymus ESTs generated in this study, 237 (79.5%) have no similarity to current data base entries. This would suggest that our collection contains approximately 100 new coding regions from thymus tissue, a large proportion of which likely will represent the middle regions of genes. The mapped ESTs should prove useful as new gene-based markers for mapping and candidate gene hunting, particularly when anchored to a well-developed physical map of the human genome.
10.1101/gr.5.4.359